Pengembangan Handout Mikrobiologi Berdasarkan Hasil Penelitian Antagonisme Kapang Antagonis terhadap Kapang Patogen pada Tanaman Buah Naga (Hylocereus sp.) - Aziz Tanama; Utami Sri Hastuti; Abdul Gofur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This research aims to produce teaching materials in the form of valid and practical Microbiology handouts based on the research